TEACHING READING BY USING TEA PARTY STRATEGY TO THE EIGHTH GRADE STUDENTS - SANI, HARITSAH; SAPUTRA, EKO (Sriwijaya University Learning and Education International Conference, 2016)
The aims of this quasi experimental study were to investigate whether or not there was (1) a significant improvement of studentsâ reading comprehension achievement after being taught by using Tea Party strategy, and (2) the significant difference of reading comprehension achievement between the students who were taught by using Tea Party strategy and those who were not. The population of this study was 282 eighth graders of one state junior high school in Palembang. The sample chosen was 60 students who were divided equally to the experimental and control groups. In collecting the data, pretest and posttest that consisted of 40 items were given to both groups. The result showed that there was a significant improvement in studentsâ reading comprehension achievement after getting the treatment and there was a significant difference of the studentsâ reading comprehension achievement in both groups.